PSIHOTERAPIA NARATIVĂ - DE LA PROBLEMĂ LA SOLUŢIE - USM ADMIN (Moldova State University, 2007)
A psychotherapeutic session offers a meeting space and inner retrieval, a space of verbal and non-verbal dialogue. This study aims to present a new perspective upon the preventive and curative psychological assistance - the narrative counseling and psychotherapy. The axiom laying at the basis of narrative psychotherapy consists in a differentiation between person and problem, the problem having its own identity and its own characteristics that are explored during the collaboration between client and psychotherapist. The fairytale-problem that the client comes with to the psycho- therapeutic session is transformed into a fairytale-solution and thus the client gets the possibility to become author of his/her own existential fairytale. With the help of the psychotherapist, the client begins to discern the factors and impacts that have led to the emergence of the problem and is able to rewrite the scenario of his/her life.